2013
DOI: 10.1155/2013/392434
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Attenuates Poststroke Depression and Increases Neurogenesis in Female Ovariectomized Rats

Abstract: Studies have linked neurogenesis to the beneficial actions of specific antidepressants. However, whether 17β-estradiol (E2), an antidepressant, can ameliorate poststroke depression (PSD) and whether E2-mediated improvement of PSD is associated with neurogenesis are largely unexplored. In the present study, we found that depressive-like behaviors were observed at the first week after focal ischemic stroke in female ovariectomized (OVX) rats, as measured by sucrose preference and open field test, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Estradiol increases neurogenesis in the SVZ of adult male Zheng et al, 2013; Table 2) and adult ovariectomized female (Suzuki et al, 2009;Cheng et al, 2013;Khan et al, 2015; Table 2) rats and mice after brain ischemia and in diabetic mice (Saravia et al, 2006). The hormone also increases neurogenesis in the SGL of ovariectomized female mice and rats Cheng et al, 2013) submitted to brain ischemia, in the SGL of diabetic mice (Saravia et al, 2006) and in the SGL of rats with hypertensive encephalopathy (Pietranera et al, 2015; Table 2). Althoigh both ERα and ERβ are involved in the regulation of neurogenesis by estradiol, in hypertensive rats the ERβ agonist DPN is more active in increasing neurogenesis than the ERα agonist 4,4′,4″-(4-propyl-[1H]-pyrazole-1,3,5-triyl)trisphenol (PPT) (Pietranera et al, 2016).…”
Section: Neurogenesismentioning
confidence: 99%
“…Estradiol increases neurogenesis in the SVZ of adult male Zheng et al, 2013; Table 2) and adult ovariectomized female (Suzuki et al, 2009;Cheng et al, 2013;Khan et al, 2015; Table 2) rats and mice after brain ischemia and in diabetic mice (Saravia et al, 2006). The hormone also increases neurogenesis in the SGL of ovariectomized female mice and rats Cheng et al, 2013) submitted to brain ischemia, in the SGL of diabetic mice (Saravia et al, 2006) and in the SGL of rats with hypertensive encephalopathy (Pietranera et al, 2015; Table 2). Althoigh both ERα and ERβ are involved in the regulation of neurogenesis by estradiol, in hypertensive rats the ERβ agonist DPN is more active in increasing neurogenesis than the ERα agonist 4,4′,4″-(4-propyl-[1H]-pyrazole-1,3,5-triyl)trisphenol (PPT) (Pietranera et al, 2016).…”
Section: Neurogenesismentioning
confidence: 99%
“…The rats were placed into the tank at the most distal location to the target quadrant where the platform had been previously located. The percentage of time spent in the target quadrant was recorded (Cheng et al, 2013).…”
Section: Morris Water Maze Testmentioning
confidence: 99%
“…This effect is possible due to the presence of estrogen receptors, ER β and ER α in the DG [ 59 , 75 ]. Evidence has shown that both ER α and ER β receptors are involved in the improvement of AHN in rats [ 26 , 76 ]. However, ER β agonists result in a greater neurogenic response, suggesting that ER β may be more strongly associated with AHN than ER α [ 75 ].…”
Section: Neurobiology Of Anxiety: Differences Between Males and Fementioning
confidence: 99%
“…Although other female gonadal hormones like progesterone [ 73 , 79 ] and LH [ 77 ] can also lead to improvements in AHN, estrogens are the most widely studied class of gonadal hormones, especially estradiol, the most potent form of estrogen [ 75 ]. Several articles have shown significant increases in the proliferation and survival of newly born neurons in the hippocampus after treatment with estradiol [ 13 , 59 , 73 , 76 , 80 , 81 ], but not with other estrogens, such as estrone [ 14 , 75 ]. In addition, during the proestrus phase of the estrous cycle, where estradiol levels are higher, rats exhibit about 50% higher proliferation than rats during diestrus and estrus stages when estradiol is low [ 82 ].…”
Section: Neurobiology Of Anxiety: Differences Between Males and Fementioning
confidence: 99%